Opportunities and Challenges of Application of big data in Bangladesh context - Marzan Rahman (Academic Journal on Science, Technology, Engineering & Mathematics Education, 2022)
This paper initiates a research effort to begin examining big data issues, opportunities and challenges. “Big Data” originally meant the volume of data that could not be processed (efficiently) by traditional database methods and tools. Big Data mining is the capability of extracting useful information from these large datasets or streams of data, that due to its volume, variability, and velocity, it was not possible before to do it. Big Data is extremely valuable to enhance the productivity in businesses and evolutionary breakthroughs in scientific disciplines, which give us a lot of opportunities to make great progresses in many fields. This study explores the big data issues and also throws light on big data applications, it’s opportunities and challenges. This study also analyze how the application of big data help to provide the customized solution to customers and grab the market share .Explorative research design and secondary data were used for this study. The available literature shows that customized marketing programs, better decision making, innovate new products are the most significant challenges. On the other hand, privacy, skill requirement, analytical and technical challenges are the most important obstacle to the application of big data in Bangladesh. But still, company and every sector should manage the challenges and implement the big data application for their goal achievement.